Metformin and Alzheimer's disease, dementia and cognitive impairment: a systematic review protocol. (August 2017) - Campbell, Jared M.; Stephenson, Matthew D.; de Courten, Barbora; Chapman, Ian; Bellman, Susan M.; Aromataris, Edoardo
Abstract : Review question/objective: The objective of the review is to assess the effect of metformin on the risk, progression and severity of Alzheimer's disease and other forms of dementia, as well as any measures of cognitive performance or impairment.